Profil pemberian nifedipine kombinasi metildopa dan MgSO4 pada pasien pre-eklamsi berat di Rumah Sakit Daerah Mangusada Badung - Diana Putri; Agung Nova Mahendra; Agung Wiwiek Indrayanti; Gede Wirata (DiscoverSys Inc., 2020)
Background: Nifedipine are recommended as first line drug choice for gestational hypertensior or severe pre-eclampsia to reduce coroner insufisiency (pectoral angina ofter cardiac infark). Aim: The study aims to determine the usage pattern of nifedipine combined with methyldopa and MgSO4 for patients with severe pre-eclampsia in RSD Mangusada Badung.Method: This study is a descriptive study with crossectional method for using the data of patient who seek treatment for severe pre-eclampsia at RSD Mangusada Badung in 2019. Nifedipine with some kind of combination aspecially anticonvulsant MgSO4 are given in the range of 2-4 days which is nifedipine are given orally and the MgSO4 are given by using IV line as a loading dose for the first step and maintenance treathment by infusion drip with appropriate monitoring. There were no monotherapy of nifedipine are found but using MgSO4 as a protocol for all the patient (100%) with severe pre-eclampsia as a convulsion prophylaxis.Results: The condision of severe pre-eclmpsia at RSD Mangusada Badung Tahun 2019 are followed by some patient’s characteristic are most prevalent in the age group of > 35 years as many as 9 people (56.25%), characteristic of pre-eclmpsia’s history as many as 5 people (55.56%), characteristic of deases history as many as 14 people (87.5%), characteristic of BMI (body mass index) are obesity degree I and II there are 11 people (68.8%) dan 4 people (25,0%) for each obesity’s character, characteristic of gestational age are most prevalent in the age group of 20-< 37 weeks as many as 10 people (62,5%) and all of them are without multiple pregnancy.Conclusion: The profile of nifedipine therapy for severe hypertension are given by using nifedipine orally combine with MgSO4 for convultion prophylaxis as a dominan result which is about 15 cases (93.75%) and all of them are showing there are no complication symptom. Nifedipine secara umum digunakan bagi pengobatan dan pencegahan insufisiensi koroner (terutama angina pektoris setelah infark jantung) dan sebagai terapi lini-1 pada hipertensi dalam kehamilan khususnya pada kejadian preeklampsia berat.Tujuan: Tujuan penelitian ini adalah untuk mengetahui profil pemberian nifedipine kombinasi metildopa dan MgSO4 pada pasien PEB (pre-eklamsi berat) di Rumah Sakit Daerah (RSD) Mangusada Badung.Metode: Penelitian ini merupakan penelitian deskriptif dengan metode crossestional pada pasien preeklamsia berat yang berobat di RSD Mangusada Badung tahun 2019. Profil pemberian nifedipine pada pasien preeklamsia berat di RSD Mangusada Badung tahun 2019 dengan pemberian terapi nifedipine dilakukan per oral dan antikonvulsan dalam hal ini MgSO4 dengan cara injeksi IV bolus dan drip. Tidak ada pemberian nifedipine monoterapi, melainkan pemberian anti konvulsan MgSO4 kepada semua pasien (100%) yang terdiagnose PEB.Hasil: Karakteristik pasien preeklamsia berat berdasarkan umur paling banyak pada kelompok usia > 35 tahun sebanyak 9 orang (56,25%) dengan pengulangan riwayat PEB/eklamsia berjumlah 5 orang (55,56%) dan paling banyak tanpa riwayat penyakit sebelumnya sejumlah 14 orang (87,5%), dengan kondisi IMT (index massa tubuh) didapatkan dominan obesitas I dan II yaitu masing-masing 11 orang (68,8%) dan 4 orang (25,0%) serta ditemukan paling banyak pada usia 20 minggu - <37 minggu yaitu 10 orang (62,5%) serta tidak ada yang memiliki kehamilan multiple.Simpulan: Profile pemberian nifedipine kombinasi dengan anti konvulsan sebanyak 15 orang (93,75%) dengan seluruhnya tidak ditemukan efek samping dan lama pengobatan di rumah sakit dengan kurun waktu 2-4 hari perawatan.